Bullying Management Strategies for Indonesia's Early Childhood Education Environment: A Bibliometric Study - Aisyah, Eny Nur; Harun, Harun; Rohman, Arif; Hardika, Hardika; Surahman, Ence (International Research-Based Education Journal, 2023)
Bullying is a behavior that is seen as very detrimental to the development of education, especially in early childhood education. This study aims to find the needs needed in the management of bullying in the early childhood learning process in Indonesia. Through the bibliometric analysis method from research results published on Google Scholar, literacy data was analyzed using Publish or Perish 8 and VOSviewer to find out the description of publications, and citations, as well as items of terms that appeared and were clustered. The results of this study show that from 980 papers published from 1799 to 2023, it was found that there were 5 clusters with 77 items of the emergence of the same term related to the development and need for bullying management in early childhood education. Further recommendations from the results of this study suggest that there is an immediate development of bullying management strategies for early childhood education that can work together in schools, homes, and communities, especially in Indonesia.